Modelling Shows the Negative Impact of Age Dependent Pharmacokinetics on the Efficacy of Oxytetracycline in Young Steers - Hekman, Peter; Schefferlie, Johan; Gehring, Ronette (Frontiers in Veterinary Science, 2022)
The effect of age dependent pharmacokinetics (PK) on the clinical efficacy of oxytetracycline (OTC) against Bovine Respiratory Disease (BRD) in beef cattle was studied, using a Physiologically Based Pharmacokinetic (PBPK) model. The model includes a bodyweight dependent renal clearance. To mimic/reproduce the long terminal half-live a bone forming tissue compartment was considered. Data for the development, calibration and validation of the model were obtained from public literature. To integrate the PK with the pharmacodynamics (PD) of OTC, Monte Carlo simulations were performed using this PBPK model to predict time-concentration curves for two commonly used dosing regimens of short-acting and long-acting injectable OTC formulations in virtual populations of 5,000 steer calves of 100 kg and 400 kg. These curves were then used to calculate the value of the PKPD index for OTC, which is the ratio of the area under the concentration-time curve for 24 h (AUC24h) over the minimum inhibitory concentration (MIC) of the target pathogen (AUC24h/MIC). The MIC values were for Mannheimia haemolytica, the dose-limiting pathogen for BRD. This integration of PBPK and PD for OTC used for the treatment of BRD in calves indicated that the Probability of Target Attainment (PTA) was sufficient for efficacy in calves of 400 kg, but insufficient for calves of 100 kg, when using a long acting dosing regimen of 20 mg/kg BW, twice, with a 48-h interval. The use of a dosing regimen of 10 mg/kg BW/day for 4 days predicted sufficient PTAs in both age groups.